Fever in the Dark : Jane Lawless #24 - Hart, Ellen (New York : Minotaur Books, 2017)
When a video of their engagement goes viral on the heels of the Supreme Court's decision to legalize gay marriage, Fiona and Annie turn for help to private investigator Jane Lawless to safeguard a secret from Annie's past.
Sequel to: The grave soul.
Keywords: Lawless, Jane (Fictitious character) -- Fiction; Women detectives -- Fiction; Secrecy -- Fiction; Lesbians -- Fiction; FICTION / LGBT / Lesbian; FICTION / Mystery & Detective / Cozy; FICTION / Mystery & Detective / Women Sleuths; Lawless, Jane (Fictitious character); Lesbians; Secrecy; Women detectives; Minneapolis (Minn.) -- Fiction; Minnesota -- Minneapolis; Detective and mystery fiction; Fiction; Detective fiction; Mystery fiction